Anodic TiO2 nanotube arrays with high surface area for dye-sensitized solar cells - Wang, Xiaoyan (2013)
Dye-sensitized solar cells (DSSCs) have received worldwide research interest as a promising and competitive candidate for low-cost photovoltaics. Highly-ordered TiO2 nanotube arrays prepared by electrochemical anodization have been developed as an intriguing photoanode owing to vertical tube alignment for one-dimensional electron transport and available inner and outer tube surface for dye attachment. For nanotubes based DSSCs, one main efficiency limitation factor is the relatively low tube surface area due to accessible large diameter (usually ~ 100 nm).